Applying a model for assessing outdoor public spaces: the case study of a city square in Maia, Portugal - Albano Joaquim Gomes Martins; Ana Vaz Sá (U.Porto Journal of Engineering)
The application of an effective and efficient model for the assessment of construction design solutions for outdoor public spaces is currently necessary for cities to obtain high quality urban spaces, be it a street, a square or a park. The characteristics of a given outdoor public space are defined by the appropriate choice of materials and construction techniques used, which must tend towards sustainable solutions. It is therefore imperative that these places are attractive in terms of urban comfort, safe to use and economically viable throughout their useful life. The model presented in this study is applicable to the design of new outdoor public spaces, as well as to the renovation of the built environment. The model has been applied to a square in the city of Maia, Portugal, which also serves to test and further develop the analysis and calculation methodology. As a main result, the square has been classified as a “good quality” outdoor public space, which is reflected in level 4 according to the proposed scale. Therefore, to further improve this space and reach the maximum level, specific improvement indicators are provided.